Solar Energy Application in Drainage Pumping Stations to Save Water and Reducing CO2 Emission. (November 2020) - Eshra, Nadia M.; Salem, Mariam G.
Abstract: Freshwater resources in Egypt are very limited. Additionally, drains are important unconventional water resources. The objectives of this paper are divided into two goals. The first goal is to save freshwater by reducing the evaporation from the drainage channels. Secondly, to reduce the CO2 emission by replacing the traditional fuel of the drainage's pump station by renewable energy. Many drainage pumps in Egypt are old and cause CO2 emission that is estimated by tons. Solar cell power represents the alternative fuel resource for these drainage pumps, it also reduces the emissions. The pump station on the Algharak drain in Egypt was studied as a sample for the drainage systems. Climate data such as solar irradiation, evaporation, air temperature, specific humidity, and wind speed were collected. The pump station data such as pump discharge, number of units, and the head were collected. Two scenarios of the pumping operation of the pump stations on Algharak drain were studied. In each scenario, the solar pumping power, area of solar cells, evaporation loss, and the value of reduction of CO2 were estimated. The results of this research could be used all over Egypt to help save a number of unconventional water resources. Graphical abstract: Highlights: The study area is Al-Fayum Oasis. Different Climate data as solar irradiation, evaporation, air temperature, specific humidity, and wind speed were collected. Two scenarios were studied of the pumping operation of the pump stations on three pump stations on Algharak drain. Calculation of the consumed power, fuel by pump stations and CO2 emission. Estimation of the solar energy required to replace fossil fuel. Calculate the evaporation from drainage channels by two different methods to be the results are more accurate. Amount of freshwater which are saving and the amount of CO2 are reducing.